Kinerja Perawat Analisis Faktor Yang Berhubungan Dengan Kinerja Perawat Di Rumah Sakit Mega Buana Kota Palopo: Analisis Faktor Yang Berhubungan Dengan Kinerja Perawat Di Rumah Sakit Mega Buana Kota Palopo - Wahyuddin, Wahyuddin; Ilyas, Muh; Saenuddin, Sudirman; Zamli, Zamli (An Idea Health Journal, 2025)
The standard of nursing care given to patients reflects good performance, which is supported by the high competence of nurses in executing their duties .This study aims to identify the factors influencing nurse performance at Mega Buana Hospital in Palopo City. “Utilizing a quantitative approach with a cross - sectional studydesign , theresearch encompassed all nurses working at Mega Buana Hospital, with a sample size of 80 nurses selected through total sampling” . Data analysis was conducted using univariate and bivariate methods, employing the Chi -Square Test for statistical analysis. The results of the study showed that there was a relationship between attitude and nurse performance at Mega Buana Hospital Palopo (p value = 0.012), there was a relationship between skills and nurse performance at Mega Buana Hospital Palopo (p value = 0.001), there was a relationship between compensation and nurse performance at Mega Buana Hospital Palopo (p value = 0.002), and there was a relationship between workload and nurse performance at Mega Buana Hospital Palopo (p value = 0.001).It is recommended that the hospital regularly provides training and guidance to nurses to enhance their skills in delivering nursing care services.”